405 nm violet-blue light inactivates hepatitis C cell culture virus (HCVcc) in ex vivo human platelet concentrates and plasma - Joseph W. Jackson; Pravin R. Kaldhone; Caitlin Stewart; John Anderson; Scott MacGregor; Michelle Maclean; Marian Major; Chintamani D. Atreya (Scientific Reports)
Abstract Added safety measures coupled with the development and use of pathogen reduction technologies (PRT) significantly reduces the risk of transfusion-transmitted infections (TTIs) from blood products. Current approved PRTs utilize chemical and/or UV-light based inactivation methods. While the effectiveness of these PRTs in reducing pathogens are well documented, these can cause tolerable yet unintended consequences on the quality and efficacy of the transfusion products. As an alternative to UV-based approaches, we have previously demonstrated that 405 nm violet-blue light exposure successfully inactivates a variety of pathogens, including bacteria, parasites, and viruses, in both platelet concentrates (PCs) and plasma. Herein, we show that 405 nm light treatment effectively inactivates hepatitis C cell culture virus (HCVcc) by up to ~ 3.8 log10 in small volumes of a variety of matrices, such as cell culture media, PBS, plasma, and PCs with 27 J/cm2 of light exposure, and total inactivation of HCVcc after 162 J/cm2 light exposure. Furthermore, we demonstrate that carry-over of media supplemented with fetal bovine serum enhances the production of reactive oxygen species (ROS), providing mechanistic insights to 405 nm light-mediated viral inactivation. Overall, 405 nm light successfully inactivates HCVcc, further strengthening this method as a novel PRT for platelets and plasma.